2013
DOI: 10.1352/1934-9556-51.3.190
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Turkish Mothers and Preschool Children With Autism

Abstract: This study explored the relationship between Turkish mothers' style of interaction and the engagement of their preschool-aged children with autism. Data were collected from fifty mother-child dyads in which all children had diagnoses of autism. Video recordings of mother-child interaction were analyzed using the Turkish versions of the Maternal Behavior Rating Scale and the Child Behavior Rating Scale (O. Diken, 2009 ). Similar to mothers from Western countries, Turkish mothers tended to engage in highly direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
(16 reference statements)
2
3
0
3
Order By: Relevance
“…In addition, there has been an increase in the areas of positive attitude and participation in the play. These results about attention drawing and nondirected interaction have been reported in the literature before (Diken & Mahoney, 2013), and the previous findings were also consistent with the findings reported in this study for NeuroPLAY. When the children were not forced by their parents during the play, it was observed that ASD severity of children could decrease when the children were included in play that was built with joint attention and a positive communication style, without commands and instructions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, there has been an increase in the areas of positive attitude and participation in the play. These results about attention drawing and nondirected interaction have been reported in the literature before (Diken & Mahoney, 2013), and the previous findings were also consistent with the findings reported in this study for NeuroPLAY. When the children were not forced by their parents during the play, it was observed that ASD severity of children could decrease when the children were included in play that was built with joint attention and a positive communication style, without commands and instructions.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, there has been an increase in the areas of positive attitude and participation in the play. These results about attention drawing and nondirected interaction have been reported in the literature before (Diken & Mahoney, 2013), and the previous findings were also consistent with the findings reported in this study for NeuroPLAY.…”
Section: Discussionsupporting
confidence: 94%
“…Autism is a complicated mental disorder. The treatment of autism often requires multiple methods and long period of time [16,17]. In this study, it was demonstrated that modified RDI combined with regular treatments might be an effective way to treat children with autism.…”
Section: Discussionmentioning
confidence: 95%
“…There are a number of studies in the literature that indicate that the interventions made by determining the nature of the parent's interactive behaviors have a positive effect on the interactional behaviors of both the parents and the children (Gürel-Selimoğlu, 2015;Karaaslan, 2010;Karaaslan, Diken and Mahoney, 2011;Mahoney 2004, 2005;Küçüker et al, 2001). When looking at these studies, it is seen that were studies with a range of working groups, ranging from mothers of children with normal development to children with mothers of different disabilities including Down syndrome , intellectual disability (Ceber-Bakkaloğlu and Sucuoğlu, 2000), developmental disability (Karaaslan et al, 2011;Küçüker et al, 2001) and ASD (Ceyhun, Özdemir, Töret and Özkubat, 2015;Diken and Mahoney, 2013, Doğan et al 2016, Gürel-Selimoğlu, 2015, Töret et al, 2014, 2015. However, it seems that these studies are usually conducted with mothers and that there are a very limited number of studies (Karaaslan, 2016a(Karaaslan, , 2016bKüçüker et al, 2001;Maviş, 2004;Taşkın and Erkan, 2009) which simultaneously examine the interaction behaviors of parent diads.…”
Section: Discussionmentioning
confidence: 99%